Ships, saints and sealore : cultural heritage and ethnography of the Mediterranean and the Red Sea - Agius, Dionisius A.; Agius, Dionisius A.; Gambin, Timothy; Gambin, Timothy; Trakadas, Athena; Trakadas, Athena; Nash, Harriet; Nash, Harriet (Archaeopress archaeology, 2014)
Just as the sea has played a pivotal role in the connectivity of people, economies and cultures, it has also provided a common platform for inter-disciplinary cooperation amongst academics. This book is a selection of conference papers and other contributions that has seen the coming-together of scholars and researchers from backgrounds as diverse as archaeology, history, ethnography, maritime and heritage studies of the Mediterranean and the Red Sea. Its strength lies in the way such diversity has been harnessed to provide an engaging and insightful study of the sea and its influences on various factors of life - both past and present